If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + -3) + x = 9x + -1 + -6x + 19 Reorder the terms: 4(-3 + 2x) + x = 9x + -1 + -6x + 19 (-3 * 4 + 2x * 4) + x = 9x + -1 + -6x + 19 (-12 + 8x) + x = 9x + -1 + -6x + 19 Combine like terms: 8x + x = 9x -12 + 9x = 9x + -1 + -6x + 19 Reorder the terms: -12 + 9x = -1 + 19 + 9x + -6x Combine like terms: -1 + 19 = 18 -12 + 9x = 18 + 9x + -6x Combine like terms: 9x + -6x = 3x -12 + 9x = 18 + 3x Solving -12 + 9x = 18 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -12 + 9x + -3x = 18 + 3x + -3x Combine like terms: 9x + -3x = 6x -12 + 6x = 18 + 3x + -3x Combine like terms: 3x + -3x = 0 -12 + 6x = 18 + 0 -12 + 6x = 18 Add '12' to each side of the equation. -12 + 12 + 6x = 18 + 12 Combine like terms: -12 + 12 = 0 0 + 6x = 18 + 12 6x = 18 + 12 Combine like terms: 18 + 12 = 30 6x = 30 Divide each side by '6'. x = 5 Simplifying x = 5
| 3p=-4p+7 | | -y+18=-32 | | 3r+3=-5 | | -5y+24=-1 | | n-21=-3(-4+7)+6n | | 7+4r=10 | | -3y-48=-7 | | 2.2=2n+0.2 | | 4y-35=-3 | | 55-10x=10x | | 5y-1=-11 | | (x+5)*(4x-4)=(x+1)*(x+1) | | 1820+230.25x=4813.25 | | 5x+35+55y= | | 6n-12=3x(2n-4) | | 14w=16(w+12) | | 21=8x+1-3x | | 4x+10=3+7-2x | | 8y+7=-9 | | -3j+9=-6j | | 2x+9+2x+9=180 | | 20.50x+175+289=1386.50 | | 2y+4(y-2)=8y-4(y-10) | | 2(x-a)=3(a+x) | | 10=5(2r-3) | | 12q=2q+40 | | 7x-12=180 | | 4+4x=-20 | | 4n+4+1+3= | | 1500+10x=3000 | | (5-x)(2x-1)=18x | | k+8=5k-16 |